A Maqasid Sharia Perspective on the Cancellation of BPJS PBI Participation Contracts in Healthcare Services: Tinjauan Maqashid Syariah Terhadap Pembatalan Akad Kepesertaan BPJS PBI Dalam Layanan Kesehatan - Suaibatul Aslamia; Rahmat Hidayat (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Health functions as a fundamental constitutional right requiring government-organized social security mechanisms. Specific Background Authorities provide medical coverage for impoverished citizens through mutual assistance agreements, yet officials frequently terminate these memberships during administrative data updates without notifying vulnerable patients. Knowledge Gap While existing literature examines legal administrative safeguards and general religious insurance concepts, comprehensive analyses evaluating unnotified medical contract cancellations specifically through targeted religious objective frameworks remain absent. Aims This normative legal study analyzes the sudden termination of social assistance clinical contracts using fundamental religious objectives. Results Administrative membership cancellations deprive poor populations of essential medical treatments and force them to pay high hospital bills. These sudden actions directly contradict the religious mandates of preserving human existence and securing personal property by threatening patient survival and exacerbating economic burdens. Novelty This research distinctly classifies government-funded medical coverage cancellations as a direct violation of mutual assistance agreements that fundamentally disrupts the religious obligation to preserve human existence and financial stability. Implications Administrative agencies must implement transparent and selective data verification procedures to guarantee uninterrupted clinical access for impoverished citizens and maintain public welfare. Highlights Government-sponsored medical coverage operates as a mutual assistance social agreement for impoverished citizens. Unnotified membership cancellations force vulnerable patients to bear unaffordable treatment costs independently. Administrative authorities must ensure transparent data verification to guarantee uninterrupted clinical access. Keywords Maqashid Syariah; Mutual Assistance; Medical Access; Contract Cancellation; Social Security